Seven minutes in heaven - Shepard, Sara, 1977- (Shepard, Sara, 1977- Lying game novel, 2013)
"Sutton Mercer had the perfect life, great friends, and a gorgeous boyfriend...until someone murdered her. Then the killer forced Sutton's long-lost twin sister, Emma, to pretend to be her. Now Sutton can only watch from beyond the grave as Emma frantically tries to figure out who killed her sister, and why. But when Sutton's body is discovered, Emma's time is up--and she becomes the number-one suspect herself."--Publisher's statement on Amazon.com.